Mimosa pudica L., a High‐Value Medicinal Plant as a Source of Bioactives for Pharmaceuticals. Issue 2 (15th December 2015) - Muhammad, Gulzar; Hussain, Muhammad Ajaz; Jantan, Ibrahim; Bukhari, Syed Nasir Abbas
Abstract: Mimosa pudica Linn. (Family: Mimosaceae ) is used as an ornamental plant due to its thigmonastic and nyctinastic movements. M. pudica is also used to avoid or cure several disorders like cancer, diabetes, hepatitis, obesity, and urinary infections. M. pudica is famous for its anticancer alkaloid, mimosine, along with several valuable secondary metabolites like tannins, steroids, flavonoids, triterpenes, and glycosylflavones. A wide array of pharmacological properties like antioxidant, antibacterial, antifungal, anti‐inflammatory, hepatoprotective, antinociceptive, anticonvulsant, antidepressant, antidiarrheal, hypolipidemic activities, diuretic, antiparasitic, antimalarial, and hypoglycemic have been attributed to different parts of M. pudica . Glucuronoxylan polysaccharide extruded from seeds of M. pudica is used for drug release formulations due to its high swelling index. This review covers a thorough examination of functional bioactives as well as pharmacological and phytomedicinal attributes of the plant with the purpose of exploring its pharmaceutical and nutraceutical potentials.